INTERFACE TWO-CHANNEL PORTABLE SYSTEM FOR 24 HOUR REGISTRATION OF BREATHING AND NASAL CYCLE - A. Atanasov; G. Arabadgiev; P. Zagorchev (Trakia Journal of Sciences)
The registration of respiration through the left and right nostrils simultaneously makes it possible to register the dynamics and periodicity of the nasal cycle. For this purpose, an interface two-channel portable system has been developed for 24-hour recording of breathing through the two nostrils separately. The portable system can be used for multifunctional medical examinations under any conditions in patients with various anatomical and physiological disorders of breathing, sleep, and consciousness.